Reformation af grundtvigianismen - Mortensen, Viggo (Grundtvig-studier, 1983)
The Reformation of Grundtvigianism By Viggo MortensenA review of The Vartov Book 1982, published by Kirkeligt Samfunds Forlag. This yearbook is a forum for all-round discussion and open debate. It does not regard the Bible as an a-historical heaven-sent book, but contains reliably informative articles, amongst others a narrative account by Finn Jacobi of the stories concerning Mary, the mother of Jesus. Two other articles attempt to read Grundtvig in the light of K. E. Løgstrup by drawing their theoretical basis from Løgstrup in order to reform the rigidified grundtvigianism.Løgstrup’s theology, according to Ole Jensen, is a modern grundtvigian theology. The grundtvigianism that was victorious in the last century was in fact victorious unto death, insofar as it forgot the critical barb in Grundtvig’s concept of folkelighed (that which is of the people). But Ole Jensen finds this criticism revitalized in L.gstrup’s posthumous essay collection System and Symbol from 1982. Svend Andersen’s article on the world-picture and the creation idea is also indirectly a criticism of those who allow a natural scientific general view to gain a monopoly on the description and interpretation of reality. He advocates a dialogue between theology and the natural sciences.